2017
DOI: 10.1177/1049909117741110
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Caregivers’ Resilience in a Terminal Cancer Care Setting

Abstract: Lack of family support is associated with and may be a cause of diminished resilience. And more concern should be paid to FCs to improve FCs' health and emotional status. Education programs might be effective for improving caregivers' resilience. Further research with supportive interventions is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(95 citation statements)
references
References 32 publications
4
84
0
4
Order By: Relevance
“…Very few studies addressing resilience in adult caregivers of adult cancer patients have been published [ 4 , 6 , 7 ]. However limited, these studies enhance the knowledge and insight into the intrinsic and extrinsic resources that either facilitate or hamper resilience after having lost a family member diagnosed with advanced cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few studies addressing resilience in adult caregivers of adult cancer patients have been published [ 4 , 6 , 7 ]. However limited, these studies enhance the knowledge and insight into the intrinsic and extrinsic resources that either facilitate or hamper resilience after having lost a family member diagnosed with advanced cancer.…”
Section: Resultsmentioning
confidence: 99%
“…major depression, anxiety, fatigue, sleeplessness or social isolation) [3], while others will not experience the diagnosis as a traumatic event [4]. However, after a short period of disruption, a significant group will probably follow a resilient process, characterised by recovery to a status of healthy functioning, or will even find benefits in caregiving [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, studies have indicated that individuals with lower resiliency are more likely to suffer from anxiety. Despite threats and unfavorable environmental conditions, resilient individuals can successfully adapt themselves to circumstances [44, 45]. Therefore, it can be inferred that resilient individuals’ self-efficacy decreases less seriously in encountering with unexpected events.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on other kinds of caregivers have highlighted the importance of family support. For example, a study conducted on caregivers' resilience in a cancer care setting found that lack of family support may lead to lower resilience (Hwang et al 2018). Another study involving caring for aging parents in Japan indicated that social support is important for family caregivers (Kikuzawa 2016).…”
Section: Discussionmentioning
confidence: 99%